Nonsusceptibility to Ceftazidime or Cefepime Can Predict Carbapenemase-Production Among Carbapenem-Resistant Pseudomonas aeruginosaa. (October 2020) - Vallabhaneni, Snigdha; Huang, Jennifer; Grass, Julian; Malik, Sarah; Bhatnagar, Amelia; Kallen, Alexander; Nazarian, Elizabeth; Morris, Shannon; Wang, Chun; Lee, Rachel; Koag, Myong; Garcia, Bobbiejean; et al.
Abstract : Background: In the United States, carbapenemases are rarely the cause of carbapenem resistance in Pseudomonas aeruginosa. Detection of carbapenemase production (CP) in carbapenem-resistant P. aeruginosa (CRPA) is critical for preventing its spread, but testing of many isolates is required to detect a single CP-CRPA. The CDC evaluates CRPA for CP through (1) the Antibiotic Resistance Laboratory Network (ARLN), in which CRPA are submitted from participating clinical laboratories to public health laboratories for carbapenemase testing and antimicrobial susceptibility testing (AST) and (2) laboratory and population-based surveillance for CRPA in 8 sites through the Emerging Infection Program (EIP). Objective: We used data from ARLN and EIP to identify AST phenotypes that can help detect CP-CRPA. Methods: We defined CRPA as P. aeruginosa resistant to meropenem, imipenem, or doripenem, and we defined CP-CRPA as CRPA with molecular identification of carbapenemase genes ( bla KPC, bla IMP, bla NDM, or bla VIM). We applied CLSI break points to 2018 ARLN CRPA AST data to categorize isolates as resistant, intermediate, or susceptible, and we evaluated the sensitivity and specificity of AST phenotypes to detect CP among CRPA; isolates that were intermediate or resistant were called nonsusceptible. Using EIP data, we assessed the proportion of isolates tested for a given drug in clinical laboratories, and we applied definitions to evaluate performance and number needed to test to identify a CP-CRPA. Results: Only 203 of 6, 444 of CRPA isolates (3%) tested through AR Lab Network were CP-CRPA harboring bla VIM (n = 123), bla KPC (n = 53), bla IMP (n = 16), or bla NDM (n = 13) genes. Definitions with the best performance were resistant to ≥1 carbapenem AND were (1) nonsusceptible to ceftazidime (sensitivity, 93%; specificity, 61%) (Table 1) or (2) nonsusceptible to cefepime (sensitivity, 83%; specificity, 53%). Most isolates not identified by definition 2 were sequence type 111 from a single-state bla VIM CP-CRPA outbreak. Among 4, 209 CRPA isolates identified through EIP, 80% had clinical laboratory AST data for ceftazidime and 96% had clinical laboratory AST data for cefepime. Of 967 CRPA isolates that underwent molecular testing at the CDC, 7 were CP-CRPA; both definitions would have detected all 7. Based on EIP data, the number needed to test to identify 1 CP-CRPA would decrease from 135 to 42 for definition 1 and to 50 using definition 2. Conclusions: AST-based definitions using carbapenem resistance combined with ceftazidime or cefepime nonsusceptibility would rarely miss a CP-CRPA and would reduce the number needed to test to identify CP-CRPA by >60%. These definitions could be considered for use in laboratories to decrease the testing burden to detect CP-CRPA. Funding: None Disclosures: In the presentation we will discuss the drug combination aztreonam-avibactam and acknowledge that this drug combination is not currently FDA approved.